Barriers in everyday life of Ukrainians with disabilities during the full-scale Russian invasion of Ukraine - Lavreniuk S. R.; Odusanvo V. T. (Український соціум)
The article provides an analysis of the barriers faced by people with disabilities in their daily lives during the full-scale Russian invasion of Ukraine. The primary focus is on the study of the everyday barriers that impede access to infrastructure, social security, personal autonomy, healthcare, and financial stability for this socially vulnerable group, with an emphasis on the exacerbation of these issues during wartime. The study is based on an analysis of academic literature that identifies social and economic barriers, as well as empirical data collected through in-depth interviews with 13 respondents with disabilities. According to results of study, significant structural barriers, such as insufficient support during evacuation, limited access to essential resources, and difficulties in accessing necessary services in frontline areas, are revealed. The research also sheds light on individual challenges associated with forced displacement, deteriorating mental health, and financial instability, which increase the vulnerability of people with disabilities during crises. Psychological barriers, including increased stress caused by isolation, fear of shelling, and increased dependence on others, are also addressed,. The conclusions emphasize that structural inequality and a lack of adaptive systems hinder equal access to services and resources for people with disabilities during war. Recommendations cover four levels: government policies to improve access to emergency services and ensure unobstructed evacuation; societal initiatives to reduce stigmatization; targeted healthcare reforms to provide continuous access to medical services; and employment programs to promote inclusive workplaces for people with disabilities. The conclusions relatively how war exacerbates social inequalities are made, the urgent need for effective inclusive policies to protect the rights and dignity of people with disabilities in Ukraine is highlighted.